2024
DOI: 10.1001/jamapsychiatry.2023.5045
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Incident Prescriptions for Behavioral Health Medications in the US, 2018-2022

Grace Chai,
Jing Xu,
Sonal Goyal
et al.

Abstract: ImportanceThe COVID-19 pandemic reportedly increased behavioral health needs and impacted treatment access.ObjectiveTo assess changes in incident prescriptions dispensed for medications commonly used to treat depression, anxiety, attention-deficit/hyperactivity disorder (ADHD), and opioid use disorder (OUD), before and during the COVID-19 pandemic.Design, Setting, and ParticipantsThis was a cross-sectional study using comprehensive, population-level, nationally projected data from IQVIA National Prescription A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Conversely, the Psychopharmacological category (including stimulant medication) had proportional rises in the early intervals of the COVID-19 pandemic (from 14.38% of posts and comments about compensation strategies on r/ADHD in 2019 to 20.73% in 2020) and an overall upsurge in content from 2020-2022. Given the disruptions to care services caused by COVID-19, these temporal trends could instead imply a reliance on ADHD medication as a more accessible form of symptom management, which is consistent with evidence showing stimulant prescription growth throughout COVID-19 [49]. Additionally, COVID-19 saw burgeoning general consumption rates for psychotropic substances (e.g., alcohol [50]).…”
Section: R/adhd Compensation Strategies and Covid-19mentioning
confidence: 58%
“…Conversely, the Psychopharmacological category (including stimulant medication) had proportional rises in the early intervals of the COVID-19 pandemic (from 14.38% of posts and comments about compensation strategies on r/ADHD in 2019 to 20.73% in 2020) and an overall upsurge in content from 2020-2022. Given the disruptions to care services caused by COVID-19, these temporal trends could instead imply a reliance on ADHD medication as a more accessible form of symptom management, which is consistent with evidence showing stimulant prescription growth throughout COVID-19 [49]. Additionally, COVID-19 saw burgeoning general consumption rates for psychotropic substances (e.g., alcohol [50]).…”
Section: R/adhd Compensation Strategies and Covid-19mentioning
confidence: 58%
“…The incident prescription was defined as a prescription with no previous transaction within the same drug class within a year (365 days). 38 The index date was defined as the day an individual received their first sedative prescription. Individuals who received sedatives or an opioid in the 365 days preceding the index date were excluded from this cohort.…”
Section: Methodsmentioning
confidence: 99%
“…In Israel Frangou et al found COVID-19 was associated with an increase in antidepressant prescription fills [30] . Using data from the IQVIA National Prescription Audit in the US, Chai et al found no significant change in trend for new antidepressant prescriptions through March 2022 [35] . Wolfschlang et al found no observed change in psychotropic or antidepressant medications in one Swedish region [36] .…”
Section: Findings In Contextmentioning
confidence: 99%